Pengaruh Terpaan Kampanye Iklan American Eagle Outfitters dan Reputasi Sydney Sweeney sebagai Human Brand terhadap Keputusan Pembelian dengan Brand Attitude sebagai Variabel Mediasi - Anindhita Shahirah; wiwid Noor Rakhmad (Interaksi Online, 2026)
The fashion industry heavily relies on advertising strategies to build brand image, yet utilizing controversial celebrities can pose fatal reputational risks for a company. This study aims to analyze the impact of American Eagle Outfitters' advertising campaign featuring Sydney Sweeney, along with her reputation as a human brand, on consumer purchase decisions, with Brand Attitude serving as a mediating variable. Employing a quantitative approach with an explanatory design, data were collected via questionnaires distributed to a number of consumers in major Indonesian cities who were exposed to the campaign, and subsequently analyzed using structural equation modeling. The findings reveal interesting and non-linear dynamics. Ad exposure does not have a significant direct effect on purchase decisions, indicating that mere frequency of viewing is insufficient to drive buying action if the delivered message is problematic. Conversely, the controversial reputation of the celebrity actually exerts a significant positive direct influence on purchase decisions, a phenomenon likely driven by curiosity stemming from massive media exposure. However, overall, this campaign successfully generates a negative Brand Attitude among consumers. This negative attitude is proven to be a strong deterrent to consumer purchase intentions. Furthermore, Brand Attitude successfully mediates the relationship between the human brand's reputation and the purchase decision, but fails to mediate the relationship between ad exposure and the purchase decision. In conclusion, the success of celebrity marketing communication in the digital era is not merely measured by popularity reach, but heavily depends on the alignment of moral values between the figure and the target audience. Ambiguous or controversial ad messages can easily damage consumer perception, ultimately thwarting the commercial objectives intended by the brand.